The Genealogic Tree of Mycobacteria Reveals a Long-Standing Sympatric Life into Free-Living Protozoa - Lamrabet, Otmane; Merhej, Vicky; Pontarotti, Pierre; Raoult, Didier; Drancourt, Michel (PLOS ONE, 2012)
Free-living protozoa allow horizontal gene transfer with and between the microorganisms that they host. They host mycobacteria for which the sources of transferred genes remain unknown. Using BLASTp, we searched within the genomes of 15 mycobacteria for homologous genes with 34 amoeba-resistant bacteria and the free-living protozoa Dictyostelium discoideum. Subsequent phylogenetic analysis of these sequences revealed that eight mycobacterial open-reading frames (ORFs) were probably acquired via horizontal transfer from beta- and gamma-Proteobacteria and from Firmicutes, but the transfer histories could not be reliably established in details. One further ORF encoding a pyridine nucleotide disulfide oxidoreductase (pyr-redox) placed non-tuberculous mycobacteria in a clade with Legionella spp., Francisella spp., Coxiella burnetii, the ciliate Tetrahymena thermophila and D. discoideum with a high reliability. Co-culturing Mycobacterium avium and Legionella pneumophila with the amoeba Acanthamoeba polyphaga demonstrated that these two bacteria could live together in amoebae for five days, indicating the biological relevance of intra-amoebal transfer of the pyr-redox gene. In conclusion, the results of this study support the hypothesis that protists can serve as a source and a place for gene transfer in mycobacteria.